Measuring effective monetary policy conservatism - Michael Berlemann; Kai Hielscher (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
According to the game-theoretic model of monetary policy, inflation is the consequence of time-inconsistent behavior of the monetary authority. The inflation bias can be eased by handing over the responsibility for monetary policy to an independent central bank and appointing a weight-conservative central banker. Countries around the world chose different combinations of central bank independence and conservatism. Most of the existing empirical studies concentrate on measuring legal or factual central bank independence thereby neglecting the degree of conservatism of the monetary authorities. In this paper we show how a joint empirical measure of central bank independence and conservatism can be derived from factual central bank behavior. Based on a panel logit approach we estimate measures of effective monetary policy conservatism for a sample of 11 OECD countries.
urn:nbn:de:gbv:705-opus-19240
Keywords: E31; E58; 330; Central Banking; Conservatism; Central Bank Independence; Inflation; Geldpolitik; Zentralbankautonomie; Inflationsbekämpfung; Messung; Theorie; OECD-Staaten